Labor Versus Empire - Smith, David; Price, Vivian; Fernandez, Raul A.; Gonzalez, Gilbert G. (Taylor and Francis, 2004)
The essays in this collection address issues significant to labor within regional, national and international contexts. Themes of the chapters will focus on managed labor migration; organizing in multi-ethnic and multi-national contexts; global economics and labor; global economics and inequality; gender and labor; racism and globalization; regional trade agreements and labor